Decentering social innovation: the value of dispersed institutes in higher education - Lough, Benjamin J. (Social Enterprise Journal, 2021)
Purpose – This paper aims to illustrate how dispersed institutes of social innovation operating as intermediary actors within higher education institutions (HEIs) may help overcome many of the institutional bureaucracies and structures that inhibit social innovation in higher education.
Keywords: Version libre-accès ResearchGate

Decentering social innovation: the value of dispersed institutes in higher education - Lough, Benjamin J. (Social Enterprise Journal, 2021)
Purpose – This paper aims to illustrate how dispersed institutes of social innovation operating as intermediary actors within higher education institutions (HEIs) may help overcome many of the institutional bureaucracies and structures that inhibit social innovation in higher education.
Keywords: Version libre-accès ResearchGate